The impact of monetary policy shocks on commodity prices - Alessio Anzuini; Marco J. Lombardi; Patrizio Pagano (European Central Bank (ECB), 2010)
Global monetary conditions have often been cited as a driving factor of commodity prices. This paper investigates the empirical relationship between US monetary policy and commodity prices by means of a standard VAR system, commonly used in analysing the effects of monetary policy shocks. The results suggest that expansionary US monetary policy shocks drove up the broad commodity price index and all of its components. While these effects are significant, they however do not appear to be overwhelmingly large. This finding is also confirmed under different identification strategies for the monetary policy shock.
Keywords: E31; E40; C32; 330; monetary policy shock; Oil Price; VAR; Geldpolitik; Schock; Rohstoffpreis; Ölpreis; VAR-Modell; USA